Enhanced Inflammation without Impairment of Insulin Signaling in the Visceral Adipose Tissue of 5α-Dihydrotestosterone-Induced Animal Model of Polycystic Ovary Syndrome - Milutinović, Danijela Vojnović; Nikolić, Marina; Veličković, Nataša; Djordjevic, Ana; Bursać, Biljana; Nestorov, Jelena; Teofilović, Ana; Antić, Ivana Božić; Macut, Jelica Bjekić; Zidane, Abdulbaset Shirif; Matić, Gordana; Macut, Djuro (Experimental and Clinical Endocrinology & Diabetes, 2017)
Polycystic ovary syndrome is a heterogeneous endocrine and metabolic disorder associated with abdominal obesity, dyslipidemia and insulin resistance. Since abdominal obesity is characterized by low-grade inflammation, the aim of the study was to investigate whether visceral adipose tissue inflammation linked to abdominal obesity and dyslipidemia could lead to impaired insulin sensitivity in the animal model of polycystic ovary syndrome.Female Wistar rats were treated with nonaromatizable 5α-dihydrotestosterone pellets in order to induce reproductive and metabolic characteristics of polycystic ovary syndrome. Glucose, triglycerides, non-esterified fatty acids and insulin were determined in blood plasma. Visceral adipose tissue inflammation was evaluated by the nuclear factor kappa B intracellular distribution, macrophage migration inhibitory factor protein level, as well as TNFα, IL6 and IL1β mRNA levels. Insulin sensitivity was assessed by intraperitoneal glucose tolerance test and homeostasis model assessment index, and through analysis of insulin signaling pathway in the visceral adipose tissue.Dihydrotestosterone treatment led to increased body weight, abdominal obesity and elevated triglycerides and non-esterified fatty acids, which were accompanied by the activation of nuclear factor kappa B and increase in macrophage migration inhibitory factor, IL6 and IL1β levels in the visceral adipose tissue. In parallel, insulin sensitivity was affected in 5α-dihydrotestosterone-treated animals only at the systemic and not at the level of visceral adipose tissue.The results showed that abdominal obesity and dyslipidemia in the animal model of polycystic ovary syndrome were accompanied with low-grade inflammation in the visceral adipose tissue. However, these metabolic disturbances did not result in decreased tissue insulin sensitivity.
Keywords: PCOS; 5α-dihydrotestosterone; visceral adipose tissue; inflammation; insulin resistance